2010
DOI: 10.1073/pnas.1009284107
|View full text |Cite
|
Sign up to set email alerts
|

RNA-dependent control of gene amplification

Abstract: We exploit the unusual genome organization of the ciliate cell to analyze the control of specific gene amplification during a nuclear differentiation process. Ciliates contain two types of nuclei within one cell, the macronucleus and the micronucleus; and after sexual reproduction a new macronucleus is formed from a micronuclear derivative. During macronuclear differentiation, most extensive DNA reorganization, elimination, and fragmentation processes occur, resulting in a macronucleus containing short DNA mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 37 publications
1
68
1
Order By: Relevance
“…Zhu et al [10] have shown that the rRNA gene copy numbers of various eukaryotic organisms are highly correlated with cell size, ranging from 1 to more than 12,000 for cell sizes of 0.8-60 lm. In the case of ciliates, Tetrahymena thermophila (40-50 lm) has *9,000 copies per macronucleus [13] and Stylonychia lemnae (230 lm) has *200,000 copies per macronucleus [14]. It has been reported that there is a strong correlation between rRNA gene copy number and genome size in eukaryotes [15].…”
Section: Discussionmentioning
confidence: 97%
“…Zhu et al [10] have shown that the rRNA gene copy numbers of various eukaryotic organisms are highly correlated with cell size, ranging from 1 to more than 12,000 for cell sizes of 0.8-60 lm. In the case of ciliates, Tetrahymena thermophila (40-50 lm) has *9,000 copies per macronucleus [13] and Stylonychia lemnae (230 lm) has *200,000 copies per macronucleus [14]. It has been reported that there is a strong correlation between rRNA gene copy number and genome size in eukaryotes [15].…”
Section: Discussionmentioning
confidence: 97%
“…However, in species such as the spirotrichous ciliates, heavy DNA fragmentation creates extremely short chromosomes that typically carry single genes, and different MAC chromosomes may be present in different copy numbers, resulting in different ploidies of these genes. While early DNA reassociation kinetic studies suggested that most of the gene-sized chromosomes in spirotrichous species are present in close copy numbers (Ammermann et al, 1974;Lauth et al, 1976;Steinbreuck et al, 1981), other studies found that genes could be present in significantly different copy numbers (Baird and Klobutcher, 1991;Donhoff and Klein, 1996;Erbeznik et al, 1999;Frels et al, 1996;Herrick et al, 1987;La Terza et al, 1995;Skovorodkin et al, 2001), and these differences were created during MAC development (Donhoff and Klein, 1996;Heyse et al, 2010). However, it was also found that in aging lines, various chromosomes could become dysregulated, and rise to extremely high copy numbers (Doerder and DeBault, 1978;Harper et al, 1991;Steinbrueck, 1983;Takagi and Kanazawa, 1982).…”
Section: Introductionmentioning
confidence: 91%
“…As a result, the MAC contains a lower total DNA complexity than the MIC does, but each MAC chromosome is present in multiple copies (polyploid) as opposed to the diploid MIC (for reviews, see Betermier, 2004;Prescott, 1994;Yao, 1996). The old (maternal) MAC is degraded after conjugation, although it can affect the new MAC's genetic profile epigenetically (Duharcourt et al, 1995;Heyse et al, 2010;Nowacki et al, 2008;Yao et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Selective gene amplification is frequently observed in differentiating eukaryotic cells and results in transcript number and gene product increases in a dosage-dependent manner (69). The mechanisms by which gene amplification is achieved include DSB-dependent sister chromatid fusion and repeated breakagefusion-bridge cycles evident in the dihydrofolate reductase locus of CHO cells (70), endoreplication of diptera chorion genes by multiple activation of replication origins within the same S-phase (71), RNA-template derived nanochromosome amplification in Stylonychia lemnae (72), or rolling circle amplification of extrachromosomal rDNA circles in Xenopus oocytes (73). Although in our study we could not distinguish if ERCs are more prone to TIR events, our results provide the possibility that ERC replication can be driven by impaired RNA transcript-processing suggesting that R-loops could have a physiological role in the control of gene amplification linked to nuclear differentiation events.…”
Section: Which Factors and Mechanism Would Participate In Transcription-mentioning
confidence: 99%